PV roofs as the first step towards 100% RES electricity production for Mediterranean islands: The case of Cyprus - Agathokleous, Rafaela A.; Kalogirou, Soteris A. (My University, 2021)
The challenge of integration of large scale RES to islands seems infeasible when the islands have isolated energy systems without primary fuel sources, with limited sources of RES and without energy storage systems. Cyprus island is one of these cases, which covers 93% of the energy demand using imported fossil fuels. Building sector is the second biggest energy consumer accounting for 19% of the final energy consumption. A net-metering scheme is introduced recently to promote the installation of small PV systems in buildings. This paper therefore takes the approach of analyzing various scenarios for installation of PV roof systems in existing and future households of Cyprus island until 2050. The goal is to achieve 100% renewable energy production to cover the needs of the households sector. Results show that the electricity demand of the domestic sector can be 100% covered when over 70% of the existing residential stock install 3 kW roof PV system. Even if 50% of the existing residential stock install a 3 kW PV system the required capacity from other applications (eg. PV parks) to make domestic sector 100% renewable is 191 MW, which is feasible. To ensure a smooth transition to 100% renewable energy in all sectors, significant actions should be taken for the development of renewable energy systems, sector coupling, smart grid system planning and storage technologies. The present study examines only the potential of the further use of net-metering scheme in the domestic sector and discusses the barriers to full energy transition as well.
Keywords: Renewable energy systems; 100% RES; Cyprus Electricity production; Households; Domestic